Kraštovaizdžio formavimo teisinė bazė ir aplinkos formavimo praktika - Staniūnas, Eugenijus (Journal of Architecture and Urbanism, 2008)
Legal basis of landscape formation and environmental design practice The design of an environment and its legal basis should make a harmonious whole. However, to realize this idea is not so easy. It can be perceived in the Lithuanian legal regulations. The Lithuanian law gives two different definitions of landscape. It puts designers and planners into a contradictory situation. It is noty the only problem. The terms, used in the Law on Protected Territories (one of the laws, giving the definition) are relatively rare and unusual. The laws do not describe them. The Lithuanian laws do not describe even such an important term as “ecological balance”. The task of design and planning of landscape is even more difficult when you try to understand the legal formulations of the tasks of landscape design and planning. All these features of laws open the possibility of different interpretations and discussions. They are especially active in planning practice. It is proposed in the paper to check the language of the laws and harmonize the Lithuanian regulations of landscape design and planning with the European Landscape Declaration. Article in Lithuanian. Santrauka. Regis, suprantama, kad civilizuotoje valstybėje aplinkos formavimas ir jį reglamentuojantys įstatymai turėtų sudaryti darnią visumą, tačiau realizuoti šią idėją nėra taip paprasta. Straipsnyje tai ir parodoma, nagrinėjant Lietuvos kraštovaizdžio teisinio reglamentavimo ir jo projektavimo praktikos santykį. Kalbama apie tai, kad dėl įstatymų miglotumo, reglamentų prieštaringumo aplinkos formavimo teisės ir praktikos ryšys korektiškas būti kol kas tiesiog negali. Reikšminiai žodžiai: kraštovaizdis, teisė, architektūra, miestų planavimas. First Published Online: 22 May 2013